Stock split and order composition: evidence from Indonesia - Eka Siskawati (Kulliyyah of Economics and Management Science, International Islamic University Malaysia, 2010)
The purpose of this study is to observe split effects surrounding split announcements. This study examines the splitting firms in Indonesia Stock Exchange for the period 1999 - 2008 while taking into account the wider split size from 2 for 1 until 10 for 1 split size. This study applies trading intensity as a proxy for liquidity effect. The result of this study indicated that there is higher liquidity of smallest trade size after split for all split size categories. This implies that small investors are attracted by lower price after split. Also, this study examines trading composition by computing the number of small buy and small sell order surrounding split announcement. Examination of trading composition aims to disentangle the signaling and liquidity effect surrounding the split events. Furthermore, this study finds that small buy order dominated after split trading activities which also imply liquidity enhancement. An interesting pattern exhibited by order composition of 2 for 1 split size shows that, small buy order significantly dominates the small sell order before split. This might indicate that 2 for 1 before split is driven by signaling effect, while 2 for 1 after split is partly driven by liquidity effect.